Management Approaches for Patients with Atrophic Gastritis in Outpatient Practice - Anvarovich, Djumayev Akbar (American Journal of Bioscience and Clinical Integrity, 2025)
Atrophic gastritis is a chronic pathological condition characterized by progressive loss of the gastric mucosal glands and decline of gastric secretory function. The eradication of Helicobacter pylori remains the fundamental part of treatment, since the bacterium acts as a major etiological factor. However, increasing antibiotic resistance reduces the efficacy of standard regimens. Rifaximin, a non-absorbed rifamycin derivative, demonstrates potential advantages including low resistance and high intraluminal concentration. This article analyzes the clinical use of rifaximin in outpatient management of atrophic gastritis.